PK/PD Modeling as a Tool for Predicting Bacterial Resistance to Antibiotics: Alternative Analyses of Experimental Data - M. V. Golikova; E. N. Strukova; Y. A. Portnoy; A. A. Firsov (Антибиотики и Химиотерапия, 2020)
Postexposure number of mutants (NM) is a conventional endpoint in bacterial resistance studies using in vitro dynamic models that simulate antibiotic pharmacokinetics. To compare NM with a recently introduced integral parameter AUBCM, the area under the time course of resistance mutants, the enrichment of resistant Staphylococcus aureus was studied in vitro by simulation of mono-(daptomycin, doxycycline) and combined treatments (daptomycin + rifampicin, rifampicin + linezolid). Differences in the time courses of resistant S.aureus could be reflected by AUBCM but not NM. Moreover, unlike AUBCM, NM did not reflect the pronounced differences in the time courses of S.aureus mutants resistant to 2X, 4X, 8X and 16XMIC of doxycycline and rifampicin. The findings suggested that AUBCM was a more appropriate endpoint of the amplification of resistant mutants than NM.